2017
DOI: 10.1103/physrevb.96.155208
|View full text |Cite
|
Sign up to set email alerts
|

Heitler-London model for acceptor-acceptor interactions in doped semiconductors

Abstract: The interactions between acceptors in semiconductors are often treated in qualitatively the same manner as those between donors. Acceptor wave functions are taken to be approximately hydrogenic and the standard hydrogen molecule Heitler-London model is used to describe acceptor-acceptor interactions. But due to valence band degeneracy and spin-orbit coupling, acceptor states can be far more complex than those of hydrogen atoms, which brings into question the validity of this approximation. To address this issu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 67 publications
(121 reference statements)
0
8
0
Order By: Relevance
“…The interactions between a pair of acceptors in the spherical model have been studied by Durst, et. al., in the framework of a Heitler-London model 10 ; later, they found that the inter-acceptor interactions in the same model are dominated at large distance by electric quadrupole moments 11 . For linear chains of acceptors, an independent-hole model was developed, including the contribution of cubic terms, and the existence of nontrivial single-particle topological edge states was demonstrated for finite chains, and related to band invariants of the corresponding infinite systems 12 .…”
Section: Introductionmentioning
confidence: 98%
“…The interactions between a pair of acceptors in the spherical model have been studied by Durst, et. al., in the framework of a Heitler-London model 10 ; later, they found that the inter-acceptor interactions in the same model are dominated at large distance by electric quadrupole moments 11 . For linear chains of acceptors, an independent-hole model was developed, including the contribution of cubic terms, and the existence of nontrivial single-particle topological edge states was demonstrated for finite chains, and related to band invariants of the corresponding infinite systems 12 .…”
Section: Introductionmentioning
confidence: 98%
“…It is an eight-level spectrum [see Eq. (27)] controlled by a single interaction parameter, J(R, µ) = Q 0 (µ) 2 /R 5 , where the seven excited-state energy levels are separated from the ground state by 3J, 5J, 7J, 8J, 10J, 13J, and 15J, respectively. From low energy to high, the degeneracy of these eight levels is 2, 2, 3, 1, 2, 4, 1, and 1.…”
Section: Discussionmentioning
confidence: 99%
“…The details of this procedure are provided in Appendix B of Ref. 27. The resulting radial functions are plotted in Fig.…”
Section: A Single Acceptor Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The electronic structure of a single acceptor can most simply be described by the "spherical model" [6][7][8][9], which includes spin-orbit coupling but neglects the cubic anisotropy of the host semiconductor and offers reasonable results for the electronic structure of an isolated acceptor. The interactions between a pair of acceptors in the spherical model have been studied by Durst et al in the framework of a Heitler-London model [10]; later, they found that the interacceptor interactions in the same model are dominated at large distance by electric quadrupole moments [11]. For linear chains of acceptors, an independent-hole model was developed, including the contribution of cubic terms, and the existence of nontrivial single-particle topological edge states was demonstrated for finite chains, and related to band invariants of the corresponding infinite systems [12].…”
Section: Introductionmentioning
confidence: 99%